Increasing The Level Of Protection Of Patients’ Personal Data On Telemedicine Platforms - M.A. Tursunova; S.Sh. Muminova (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This thesis provides a comprehensive analysis of data protection mechanisms in modern telemedicine platforms and identifies their main technical, legal, and human-factor vulnerabilities. As a solution to the identified problem, a holistic protection model based on the “Defense-in-Depth” concept is proposed. The proposed model integrates three main components: 1) advanced technical measures such as end-to-end encryption (E2EE) and blockchain; 2) regulatory and legal improvements, including the harmonization of HIPAA and GDPR standards and strengthening the ownership of patient data; 3) a human-factor-oriented approach, which involves continuous cybersecurity education and training for healthcare professionals and patients.